2018
DOI: 10.1183/13993003.02114-2017
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity medications and poor asthma prognosis

Abstract: Multimedication related to multimorbidity is common in the elderly with asthma. We aimed at comprehensively characterising medications used by elderly women and assessing how multimedication impacts on asthma prognosis.We performed network-based analyses on drug administrative databases to visualise the prevalence of drug classes and their interconnections among 17 458 elderly women from the Asthma-E3N study, including 4328 women with asthma. Asthma groups sharing similar medication profiles were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Our data, including 10% of adults with severe asthma, suggest that allergic multimorbidity might be more strongly associated with severe asthma than milder form of asthma, although asthma severity was not identified as a significant modifier effect given the large confidence intervals. Our results are in line with results from previous publications . Among adult women with asthma, a clustering approach using drug‐based administrative databases identified three multimorbidity patterns associated with asthma, including a pattern mainly characterized by “allergic multimorbidity” that represented 33% of the population .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data, including 10% of adults with severe asthma, suggest that allergic multimorbidity might be more strongly associated with severe asthma than milder form of asthma, although asthma severity was not identified as a significant modifier effect given the large confidence intervals. Our results are in line with results from previous publications . Among adult women with asthma, a clustering approach using drug‐based administrative databases identified three multimorbidity patterns associated with asthma, including a pattern mainly characterized by “allergic multimorbidity” that represented 33% of the population .…”
Section: Discussionsupporting
confidence: 91%
“…31 This multimorbidity profile showed an increased risk of subsequent uncontrolled asthma and asthma exacerbations as compared to a profile characterized by "few multimorbidity," and importantly, this risk was of similar magnitude than the risk observed for the "metabolic multimorbidity" profile. 31 Thus, allergic diseases affect morbidity lifelong, 32 although in terms of mortality, previous studies indicate that AR/AC did not explain excess mortality among asthmatic adults. 13 Overall, it is likely that asthma with allergic multimorbidity represents phenotypes that considerably differ from asthma alone in terms of mechanisms, severity, and prognosis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Asthma comorbid conditions are associated with substantial healthcare costs that are five times higher than costs attributable to asthma alone 9 . On top of the direct costs, asthma comorbid conditions are associated with worse asthma-related outcomes 5,10 , increased risk of work disability 11 and significant productivity losses 12 , further contributing to the burden of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that these allergic diseases and their multimorbidity in childhood are often associated with further respiratory problems in adult life, such as adult-onset asthma, lower lung function and a higher risk of chronic obstructive pulmonary disease (COPD) [40][41][42] . Further, some population-based studies have observed that those with allergic diseases have a higher prevalence of other noncommunicable diseases (NCDs), specifically cardiovascular and metabolic, both in children 43 and adults 44,45 . In addition, there is consistent evidence from populationbased studies of a significant association between asthma and attention deficit hyperactivity disorder (ADHD) both in children and adults 46,47 .…”
Section: Beyond Medallmentioning
confidence: 99%